2018
DOI: 10.1021/acsami.8b09066
|View full text |Cite
|
Sign up to set email alerts
|

Acidic Dressing Based on Agarose/Cs2.5H0.5PW12O40 Nanocomposite for Infection Control in Wound Care

Abstract: Regulation of wound pH from alkaline to acidic is a simple and powerful approach to reduce wound microbial colonization and infection. Here, we present a nanocomposite material possessing intrinsic acidic surface pH as an innovative antimicrobial wound dressing. This material comprises an agarose matrix nanocomposite containing nanoparticles (NPs) of the cesium salt of phosphotungstic heteropolyacid (Cs2.5H0.5PW12O40). Self-supporting films were prepared by a casting method incorporating 5–20 wt % Cs2.5H0.5PW1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…Besides, several polyoxometalates (POMs), which can be seen as negatively charged molecular oxides incorporating metals (mainly tungsten, molybdenum and vanadium) in high oxidation states, 20 have shown important antibacterial activity, [21][22][23][24][25][26] and notably two examples of anti-biolm POM composites have been reported in the literature. 27,28 In this context, the use of POMs as active antibacterial agents supported by AuNPs represents a promising alternative. The relevance of this approach to the elaboration of antibacterial agents is supported by the studies of Daima et al, which showed that AuNPs post-functionalized with purely inorganic commercial POMs exhibit antibacterial activity against the non-resistant E. coli bacteria.…”
mentioning
confidence: 99%
“…Besides, several polyoxometalates (POMs), which can be seen as negatively charged molecular oxides incorporating metals (mainly tungsten, molybdenum and vanadium) in high oxidation states, 20 have shown important antibacterial activity, [21][22][23][24][25][26] and notably two examples of anti-biolm POM composites have been reported in the literature. 27,28 In this context, the use of POMs as active antibacterial agents supported by AuNPs represents a promising alternative. The relevance of this approach to the elaboration of antibacterial agents is supported by the studies of Daima et al, which showed that AuNPs post-functionalized with purely inorganic commercial POMs exhibit antibacterial activity against the non-resistant E. coli bacteria.…”
mentioning
confidence: 99%
“…Affected by the human body’s internal pH of 7.4, the pH value of the unhealed skin wound fluctuates between 7 and 8, which indicates the possibility of bacterial infection . Eventually, the pH of a healed wound tends toward neutral and becomes acidic . With the emergence of flexible electronics and biomaterials, the preparation of the wound patch equipped with pH sensors and connected to smart devices has attracted a lot research interest.…”
Section: In Situ Monitoringmentioning
confidence: 99%
“… 21 It was observed that the nanocomposite films based on cesium salt of phosphotungstic heteropolyacid and agarose exhibited biocidal activity promoted by the acidic surface pH. 22 Thus, heteropolyacids can be used as a biocide in antibacterial formulations. Halloysite nanotubes (HNT) are perspective nanocarriers for biocide delivery because the charged external and inner surfaces of the nanotube are suitable for modification.…”
Section: Introductionmentioning
confidence: 99%